Energy Consumption, Economic Growth and Trade Balance in East Asia: A Panel Data Approach - Tran, Trong Nguyen; Nguyen, Thu Thuy; Nguyen, Van Chien; Vu, Thi Thu Huong (International Journal of Energy Economics and Policy, 2020)
The purpose of this work is to study the effects energy consumption, economic growth and trade balance in the East Asian countries. Using a panel data analysis in the period over 1996-2015, the study analyzes based on the methods of fixed, random effects, and pooled ordinary least squares. The data were collected from World Development Indicators, Department of Statistics in relevant countries used in the study. Our results demonstrate that energy consumption has negatively affected trade balance while economic growth that can negatively affect the balance of trade but insignificant. Further, the prime factors that can significantly impact trade balance are exports, exchange rates and development level. Both exports and exchange rates have positive and significant impacted on trade balance. Finally, a country with a higher level of domestic income will certainly perform a higher level of trade balance. Keywords: Economic growth, energy consumption, fixed effect, random effect, trade balance JEL Classifications: C58, F14, O47, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.9401